Evaluasi Penggunaan Biosaliva Dalam Deteksi Sars-Cov-2 Metode RT-PCR - Suryanata Kesuma; Suparno Putera Makkadafi (Universitas Muhammadiyah Surabaya, 2022)
SARS CoV-2 infection, which has affected the world since late 2019, can cause serious lower respiratory tract infections that may be fatal in some patients. This infection causes the disease Covid-19. The diagnosis of SARS-CoV-2 infection was carried out by NAAT (Nucleic Acid Amplification Test) such as RT-PCR examination. The sample needed for the identification of SARS-COV-2 is a nasopharyngeal/oropharyngeal swab. Nasopharyngeal/oropharyngeal swab sampling requires trained personnel. Taking a nasopharyngeal/oropharyngeal swab is invasive, causing discomfort in its implementation. The convenience of sampling specimens can be an alternative option for the identification of SARS-CoV-2, such as with newly developed biosaliva specimens. The use of this biosaliva sample can be a practical option in the examination of the identification of SARS-CoV-2. However, the use of these specimens needs to be evaluated first because of the possible relationship with clinical findings and so that the results of the SARS-CoV-2 examination are valid and reliable. The purpose of this study was to evaluate the use of biosaliva specimens to detect SARS-CoV-2 infection with the RT-PCR method. Evaluation of the use of biosaliva in the detection of SARS-COV-2 RT-PCR method with paired T test and diagnostic test with the gold standard using nasopharyngeal/oropharyngeal swabs. The target genes for the detection of SARS-CoV-2 are the RdRp gene and the E gene with control of the HRP gene. RT-PCR was carried out with 40 cycles and Tm 62 °C. The results of this study are Sig. (2-tailed) paired T test was 0.106, sensitivity was 64.86% and specificity was 90.92%. The conclusion of this study is that there is no statistical difference in the results of the SARS-CoV-2 RT-PCR method between the use of biosaliva specimens and nasopharyngeal/oropharyngeal swabs, and the evaluation results show that reliable biosaliva specimens are used as samples in the examination of SARS-COV-2 infection.